Children's sleep and fathers' health and wellbeing: A systematic review. (February 2022) - Coles, Laetitia; Thorpe, Karen; Smith, Simon; Hewitt, Belinda; Ruppanner, Leah; Bayliss, Olivia; O'Flaherty, Martin; Staton, Sally
Summary: Night-waking is typical across infancy and early childhood, inevitably disrupting family sleep. For some children, sleep problems develop and endure throughout childhood. This systematic review focused on fathers, and synthesised the evidence pertaining to the effects of children's sleep (from birth to 12 years) on fathers' health and wellbeing. A total of 29 studies were included. Key outcomes reported for fathers were: sleep and fatigue; mental and general health; and family functioning. An association between child sleep and father's sleep was observed when child's sleep was measured via actigraphy or paternal report, but not when measured via maternal report, suggesting that mothers may not always be aware of disruptions that awaken fathers. Findings showed poorer child sleep was associated with poorer general health and wellbeing among fathers, however, associations of poor child sleep with depression were fewer, and less frequent than those reported for mothers in the same households. Poor child sleep was negatively associated with the quality of family relationships, both within the couple and between parent and child. Future studies seeking to understand the interplay of child sleep and family wellbeing should apply objective measurement of sleep and integrate formal measures of family dynamics into the study design.